Jungkʼs Controversial Bestseller Brighter Than a Thousand Suns and Nazi Uranium Research - Grygar, Filip (Teorie vědy / Theory of Science, 2023)
The essay deals with Nazi uranium research in the context of Jungkʼs bestseller Brighter Than a Thousand Suns (1956). The first part of the article introduces the reader to Jungk himself, as well as to the historical-political context that crucially influenced his moralising positions in favour of the German uranium scientists (they did not build nuclear weapons for Hitler) and at the same time against the Allied scientists (they built nuclear weapons and used them). Based on historical sources (gradually made available since the 1970s), the second part of the study discusses the Nazi Uranium Clubʼs efforts to produce a uranium reactor and nuclear weapons. German scientists worked for the Nazi regime voluntarily and intensively and were fascinated by the research. The third part reveals the origins of the post-war legend of the supposedly innocent German scientists, their decades-long alibism, and the criticism of Jungkʼs bestseller by the Allied command, the scientists, and eventually Jungk himself, who put faith in the interviews in which German scientsts proclaimed their activities had been nothing but peaceful.